Master of None: TV series or food guide? In search of boundaries, between Italian stereotypes, cultural filters and Food locations - Spaziante, Lucio (E|C, 2020)
The article reflects on the role of cultural mediation played by audiovisual texts such as TV series. The example treated in this case is Master of None, the American comedy TV series (Netflix 2015-2017), conceived and interpreted by Aziz Ansari - American actor of Indian origin - which presents an ironic look on prejudices ethnic and cultural stereotypes in general. In the second season, Italy assumes a central role, with the first two episodes set in Modena, in which the protagonist makes a gastronomic journey in the Emilian cuisine and in the Italian cinema (from De Sica by Bicycle Thieves at the Antonioni de La notte). What emerges is a representation of Italy conditioned by clichés, which, depending on the audience (American, international, Italian) has obtained variable consensus. At the same time, the series has established itself in lifestyle and food and wine magazines as a sort of accredited food & travel guide for the discovery of places and places to visit, both for New York and for Italy, thus questioning the difference between a fictional text and a non-fictional text.